Morphological Study for Identification Improvement of Poeciliidae Family Based on Gonopodium structures and Morphometric analysis - Dwi Anggorowati Rahayu; Dwi Listyorini; Ibrohim Ibrohim (Journal of Tropical Life Science, 2013)
Poeciliidae family consists of small live-bearer fishes with sexual dimorphic. This fishes are widely distributed across Indonesian archipelago, but biological studies on this fish are very limited. This research is aimed to identify the species of Peciliidae fishes which lives in Sari Lake Pasuruan based on gonopodium structures and morphometric analysis. A specific characteristic of the Poeciliidae family is its gonopodium structures which is a modification of 3rd, 4th, and 5th rays of the males anal fin. Each species represented 50 samples male and female from each type we found and measured 26 characters (in mm). Cladogram based on morphometric measurements showed that sample 1 and 2 had 100% similarity, sample 3 had 94% similarity with sample 1 and 2. Sample 4 had 54% similarity with sample 1, 2, and 3. Based on gonopodium structures sample 1 and sample 2 included Xiphophorus hellerii Heckel possess large claw on the terminus of ray 5 hook is small crescent-moon shaped on 3rd ray and lacking of gonopodium palp, sample 3 possesses distal platform with 11 retrosse serrae,and membranous hook so we were able to identify the sample 3 as Poecilia mexicana Steindachner, whilst sample 4 was Poecilia reticulata Peter had a long-pointed comb-like spines on ray 3rd and and has a small hook on the tip of 5p ray.